Keragaman Aspek HOTS (Higher Order Thinking Skills) dalam Instrumen Evaluasi pada Buku Teks Bahasa Indonesia SMA Kelas X Terbitan Tiga Serangkai - Witdianti, Yeni; Marzuki, Ismail; Kalapain, Febiola (Universitas PGRI Semarang, 2024)
This research aims to reveal the diversity of HOTS (Higher Order Thinking Skills) aspects in the evaluation instrument in the Indonesian high school class Higher Order Thinking Skills) contained in the evaluation instrument for Indonesian high school class The data was taken from an evaluation instrument in the form of a 60-item essay test. The data analysis technique used in this research was content analysis There are various types of Indonesian language textbooks for class X published by Tiga Serangkai Solo. However, the distribution is not evenly distributed. The creative thinking aspect is 32 questions, the critical thinking aspect is 42 questions, the problem solving aspect is 21 questions, and the decision making aspect is 18 questions. It is necessary to strive for even distribution of HOTS (Higher Order Thinking Skills) aspects in the evaluation instrument because each aspect of thinking has a very significant contribution in developing students' thinking abilities. The more frequently students are exposed to or trained in various thinking abilities, the more skilled their thinking abilities will be.